البلدية ورهان التنمية المحلية في الجزائر قراءة في دور الدور المركزي للدولة في أداء الجماعات المحلية - بن مبروك سفيان (جامعة المسيلة, 2022)
ان من اهم المشاكل التي تواجه البلدية الجزائرية هو ضرورة حل اشكالية العجز في الميزانية البلدية، وهو ما يتحقق عن طريق ايجاد مصادر تمويل متنوعة وتثمين الموارد المالية للبلدية و التقليل من الاعتماد على اعانات الدولة , وبث روح الاتكال على النفس و على الموارد الذاتية للبلدية, وهو ما يخلق ديناميكية ايجابية تقضي على التخاذل وتساهم في الرقي بالبلدية و تحقيق التنمية المحلية المنشودة ان ا ما في أداء مهامها الإدارية إلا أنها قد فشلت في القيام بعملها في مجال التنمية المحلية ، وعليه لا بد من بحث سبل وامكانية تنشيطها حتى تتمكن من الاضطلاع بمهامها مع ضرورة وضع رؤية مستقبلية كآفاق لإصلاحها بما يتطلبه مقتضيات ذلك. ان التحدي الذي يواجه البلدية في الجزائر هو ترقيتها الى مستوى المؤسسة العصرية القادرة على تقديم الخدمات وتسريع معاملات المواطنين والتواصل المباشر معهم وتفعيل مشاركتهم وجعلها عملية مستمرة في التنمية المحلية. الكلمات المفتاحية: البلدية، التنمية المحلية. One of the most important problems facing the Algerian municipality is the need to solve the problem of the municipal budget deficit, which is achieved by finding various sources of funding, valuing the municipality’s financial resources, reducing dependence on state subsidies, and spreading the spirit of self-reliance on the municipality’s own resources, which is What creates a positive dynamic that eliminates inactivity and contributes to the advancement of the municipality and the achievement of the desired local development. However, in performing its administrative tasks, it has failed to carry out its work in the field of local development, and accordingly, ways and the possibility of activating it must be discussed so that it can carry out its tasks with the necessity of Develop a future vision as prospects for reforming it as required by the requirements of that. The challenge facing the municipality in Algeria is to raise it to the level of a modern institution Able to provide services, speed up citizens’ transactions, communicate directly with them, activate their participation, and make it a continuous process in local development. Keywords: municipality, local development.
Keywords: البلدية، التنمية المحلية.